The Role of Human Rights in Religiously Motivated Violence: An Overview of Violence Against Religious Minorities in Indonesia - Ummah, E. Ova Siti Sofwatul (UIN Sunan Kalijaga Yogyakarta, 2023)
This article aims to explain the role of human rights in conditions of conflict committed in the name of religion and to explain the basic human rights that were lost in incidents of violence committed in the name of religion. Recently, an incident of violence committed in the name of religion happened again. Violence committed in the name of religion occurs to religious groups in Indonesia, as happened to the Shia group and the Ahmadiyya group. Both groups are religious minority groups in Indonesia. They both experienced violence committed in the name of religion. The violence occurred because the two groups were outside the mainstream group and considered heretical. Therefore, the majority group felt it was appropriate to commit violence against the two groups. In addition, regional regulations or clerical fatwas also trigger violence. This article uses library research in the data collection process, for example, through journals and textbooks. Human rights certainly have several role related to prevent violence committed in the name of religion, namely the role to protect human being or religious community from murder or genocide, war in the name of religion, ethnic cleansing and violence against humanity. Therefore, human rights can encourage strengthening the message of compassion that exists in every religion and belief as a bulwark against messages of hate and violence.